Photoinduced electron transfer properties of 4-phenyl-Pyridine-N-Oxide and its coordination compound. (January 2022) - Han, Yong-Fang; Zhang, Ning-Ning; Li, Li; Xin, Liu-Di; Qu, Kong-Gang
Abstract: Photoinduced electron transfer (PET) with the formation of stable radicals plays an importance role in many areas. However, the discovery of new photoresponsive moieties is still a challenge. In this work, pyridine N -oxide group itself was demonstrated to possess photoinduced electron transfer (PET) property for the first time. The radical of 4-phenyl-pyridine- N -oxide (ppno ), generated by PET from oxygen atom to 4-phenyl-pyridine part, remained stable in dark in air at least for two weeks. [ZnCl 2 (ppno) 2 ], one ppno -based novel crystalline coordination compound, has two electron donors, chlorine and oxygen atoms. In particular, experimental and theoretical calculation results showed that oxygen atoms in [ZnCl 2 (ppno) 2 ] have dual actions. Firstly, oxygen atom as electron-withdrawing group increased the electron accepting ability of 4-phenyl-pyridine. Then, oxygen atoms themselves are rich in electrons and can act as electron donors. This is exactly why the performance of PET and radical yield and stability of [ZnCl 2 (ppno) 2 ] much better than ppno . Thus, pyridine N -oxide group as an effective photoresponsive functional motif, whether by interspersion or by coordination, could construct various novel photoresponsive materials. Graphical abstract: Image 1 Highlights: Pyridine N -oxide group itself was demonstrated to possess photoinduced electron transfer (PET) property for the first time. After the coordination, oxygen atom of ppno has dual actions. Firstly, oxygen atom as electron-withdrawing group increased the electron accepting ability of 4-phenyl-pyridine. Then, oxygen atoms themselves are rich in electrons and can act as electron donors. The coordination effect enhanced the performance of photochromism and radical yield and stability.